Situation Report: Romania, 5 April 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian Media Report on Soviet Letter to Red China Italo-Romanian Trade Talks Romanian-East German Protocol on Technical-Scientific Cooperation Romanian-Yugoslav Talks on Iron Gate Project Resumed Romanian-Hungarian Book Publishing Agreement Association of Movie-Makers Established Student Delegation to Paris Romanian Playright [Playwright] Again under Fire